Analisis Penerapan Manajemen Persediaan Bahan Baku Arm Rear Brake Kyea dengan Metode EOQ - Ferry Utama Dwi Putra; Apid Hapid Maksum; Hamdani Hamdani (Fakultas Teknik, 2022)
Inventory management is an essential aspect of supporting good production planning in company business activities. The implementation of inventory management in the company is a primary need. If there is a problem in the supply of raw materials, all the company's operational activities will be disrupted. Inventories in manufacturing usually consist of raw materials, semi-finished goods, and finished goods or final products. Inventories of arm rear brake materials for the production process often experience shortages due to immature controls. This study aims to determine the inventory control of rear arm brake raw materials using the Economy Order Quantity (EOQ) method at PT. Ciptaunggul Karya Abadi. Based on the discussion results, it was found that ordering raw materials was carried out two times a year with a total order of 621 pieces with 86 pieces of safety stock and will be ordered again when raw materials collected 21 pieces. Total Inventory Cost (TIC), which was initially Rp110.264.235,00, can be saved to Rp70.598.399,00 so that the total savings that occur are Rp39.674.899,00 which is equal to 33.26%.